Short Term Radiographic and Patient Outcomes of a Novel Biplanar Plating System for Hallux Valgus Correction. Issue 4 (16th October 2019) - Manchanda, Kshitij; Wallace, Stephen Blake; Ahn, Junho; Liu, George T.; Van Pelt, Michael D.; Raspovic, Katherine M.; Wukich, Dane K.; Lalli, Trapper
Category: Bunion, Midfoot/Forefoot Introduction/Purpose: Hallux valgus is a complex deformity of the great toe and is a major cause of pain for patients. Despite the variety of techniques, traditional osteotomies often do not address rotational deformities. A novel biplanar plating system was used to perform correction of metatarsal rotation at our institution starting in 2017. The purpose of this study was to determine the correction of rotational deformity and of radiographic parameters, maintenance of this correction (versus recurrence of hallux valgus), complication rates and patient-reported objective survey scores. We sought to determine prognostic factors for successful correction, including age, gender, and time of surgery. Methods: By retrospective chart review, we identified all patients treated by the novel biplanar plating at our institution. We recorded patient demographics, pre-operative range of motion and maltracking, surgical details, operative complications, and any subsequent surgery. Imaging was reviewed at pre-operative and post-operative visits to approximate the hallux valgus angle (HVA), intermetatarsal angle (IMA), and tibial sesamoid position (TSP). Outcome scores (AOFAS, FAAM, SF12 PCS and MCS) pre- operatively and post-operatively at 3 months, 6 months and 12 months were also recorded. The changes in these radiographic parameters and scores were then computed and analyzed to determine if there was an improvement with surgery. Results: Fifty-seven procedures (in 55 patients) were performed and evaluated. There were 8 complications and average follow- up time was 27.1 weeks (+13.8 weeks). Older age was significantly associated with more complications (p = 0.018). Gender and time of surgery did not show any significant association with complications. Radiographic parameters including HVA, IMA, and TSP were analyzed. At 3 and 6 months post-operatively, these parameters were significantly reduced from pre-operative values. At 12 months, there was a trend towards significant reduction (p values of 0.06, 0.06, and 0.053 respectively); however, there were fewer patients who maintained follow-up during this period. The Outcome scores showed improvement post-operatively, but only the AOFAS score showed statistical significance at 3 and 6 months. Conclusion: Although statistical analysis was limited due to our population size and the retrospective nature of the study, there was an overall improvement in both radiographic parameters and clinical outcome scores. Older patients are also at higher risk of complications. Malrotation correction with this biplanar plating system is a novel technique and does require meticulous training. With continued expansion of our patient database and further longitudinal analysis, we hope to determine not only if correction is maintained over time, but also if the steepness of the learning curve affects the number of complications earlier versus later in each individual surgeon's experience.